Thermal Characteristics of Eutectic Mixtures of Fatty Acids as Phase Change Material - Rozanna Dewi, (2005)
Latent heat storage in phase change material (PCM) is one of the efficient ways of storing thermal energy. In latent heat storage, energy is stored in a small mass/volume with a narrow temperature transition between melting and solidifying. This study aims to investigate the effect of using eutectic mixtures of fatty acids as PCM in building material such as gypsum board, palm-based and petrochemical-based polyurethane. Gypsum is widely used in construction industry due to its low cost. It is considered as a good supporting material for thermal energy storage since it has 41% air voids. The choice of polyurethane (PU) is made because of its increase uses in the construction industry.